Respuesta :
Answer:
- Solutions: [tex]\displaystyle\mathsf{x\:=\:\frac{7+ \sqrt{61}}{6}}[/tex] , [tex]\displaystyle\mathsf{x\:=\:\frac{7 - \sqrt{61}}{6}}[/tex]
Step-by-step explanation:
We are given the following quadratic equation, 3x² - 1 = 7x, which requires us to find its possible solutions using the quadratic formula.
Definitions:
- In a quadratic equation, the leading term has a second-degree (or squared) variable.
- The standard form of a quadratic equation is ax² + bx + c = 0, where a, b, and c are real numbers, and that a ≠ 0.
Quadratic Formula:
The quadratic formula is given by:
[tex]\displaystyle\mathsf{x\:=\:\frac{-b\pm\sqrt{b^2-4ac}}{2a}}[/tex]
We will use this formula to solve for the roots or the solution of the given quadratic equation.
Solution:
Step 1: transform the given equaton into standard form.
First, we must subtract "7x" from both sides of the equation:
3x² - 7x - 1 = 7x - 7x
3x² - 7x - 1 = 0 ⇒ This is the standard form of the given quadratic equation where a = 3, b = -7, and c = - 1.
Step 2: Plug in the values for a, b, & c into the quadratic formula.
The derived values for a, b, & c from the previous step are: a = 3, b = -7, and c = - 1. Substitute these values into the following quadratic formula:
[tex]\displaystyle\mathsf{x\:=\:\frac{-b\pm\sqrt{b^2-4ac}}{2a}}[/tex]
[tex]\displaystyle\mathsf{x\:=\:\frac{-(-7)\pm\sqrt{(-7)^2-4(3)(-1)}}{2(3)}}[/tex]
Step 3: Following the PEMDAS Order of Operations, start by applying the Power rule of Exponents [tex]\displaystyle\mathsf{(a^m)^n = (a^{m*n})}[/tex] (under the radical) :
[tex]\displaystyle\mathsf{x\:=\:\frac{-(-7)\pm\sqrt{49-4(3)(-1)}}{2(3)}}[/tex]
Step 4: Next, multiply the integers under the radical, PEMDAS Order of Operations.
[tex]\displaystyle\mathsf{x\:=\:\frac{-(-7)\pm\sqrt{61}}{2(3)}}[/tex]
Step 5: Multiply the integers in the denominator, and apply the multiplication integer rule, -(-a) = a.
[tex]\displaystyle\mathsf{x\:=\:\frac{7\pm\sqrt{61}}{6}}[/tex]
- Since [tex]\displaystyle\mathsf{\sqrt{61}}[/tex] is not a perfect square, it can remain the same.
Step 6: Separate the solutions.
[tex]\displaystyle\mathsf{x\:=\:\frac{7+ \sqrt{61}}{6}}[/tex] , and [tex]\displaystyle\mathsf{x\:=\:\frac{7 - \sqrt{61}}{6}}[/tex]
Final Answer:
Therefore, the solution to 3x² - 1 = 7x are: [tex]\displaystyle\mathsf{x\:=\:\frac{7+ \sqrt{61}}{6}}[/tex], [tex]\displaystyle\mathsf{x\:=\:\frac{7 - \sqrt{61}}{6}}[/tex].
_____________________
Keywords:
Quadratic equation
Quadratic function
Standard form
Parabola
______________________
Learn more about quadratic equations here:
https://brainly.com/question/8649555
![Ver imagen djtwinx017](https://us-static.z-dn.net/files/d6a/99e690cba8258a3388e1a8302ee7dcb1.png)